Synthesis, Tunable Multicolor Output, and High Pure Red Upconversion Emission of Lanthanide-Doped Lu2O3 Nanosheets - Lingzhen Yin; Tianmei Zeng; Zhigao Yi; Chao Qian; Hongrong Liu (Advances in Condensed Matter Physics)
Yb3+ and Ln3+ (Ln = Er, Ho) codoped Lu2O3 square nanocubic sheets were successfully synthesized via a facile hydrothermal method followed by a subsequent dehydration process. The crystal phase, morphology, and composition of hydroxide precursors and target oxides were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), and energy-dispersive X-ray spectroscope (EDS). Results present the as-prepared Lu2O3 crystallized in cubic phase, and the monodispersed square nanosheets were maintained both in hydroxide and oxides. Moreover, under 980 nm laser diode (LD) excitation, multicolor output from red to yellow was realized by codoped different lanthanide ions in Lu2O3. It is noteworthy that high pure strong red upconversion emission with red to green ratio of 443.3 of Er-containing nanocrystals was obtained, which is beneficial for in vivo optical bioimaging.